AB0099 Aberrant basal and TLR-stimulated expression of TSLP in rheumatoid synovial fibroblasts. (23rd January 2014) - Kam, N.W.; Bombardieri, M.; Filter, A.; Buckley, C.; Pitzalis, C.
Abstract : Background: Thymic stromal lymphopoietin (TSLP) is an interleukin-7-like cytokine, which strongly activated dendritic cells for Th2 polarization. Previous collagen-induced arthritis model demonstrated its role in exacerbating disease severity via T-cell dependent mechanism. Objectives: Here we investigated TSLP and its receptor (TSLPR) expression in the synovium of rheumatoid arthritis (RA) patients and in rheumatoid synovial fibroblasts (RASF), osteoarthritis fibroblast (OASF, to dissect disease specificity) as well as paired RA dermal fibroblasts (RADF, to investigate site specificity) in basal conditions and upon stimulation with Toll-like receptors (TLR) ligands. Methods: mRNA and protein (cytoplasmic and soluble) expression of TSLP in RASF, OASF and RADF, stimulated with or without TLR agonists: bLP (TLR2 ligand), PIC (TLR3 ligand) and LPS (TLR4 ligand), was assessed by Taqman PCR (QT-PCR), immunocytochemistry and ELISA. TSLP and TSLPR expression in 40 synovium of RA patients was investigated by QT-PCR and immunohistochemistry. Results: RASF and, to a lesser extent OASF, constitutively displayed higher TSLP mRNA (∼8-16 fold) compared to RADF. In vitro stimulation of TLR3 and TLR4, but not TLR2 on RASF led to strong induction of TSLP mRNA expression (∼20-fold increase with TLR3), which peaked early at 8h. Cytoplasmic staining of TSLP was increased in TLR3-activated RASF but not RADF, while soluble TSLP was time-dependently released in the supernatant of TLR3-stimulated RASF (∼100pg/ml) and undetectable in RADF. TSLP mRNA was observed in all the RA samples examined while TSLPR was significantly increased in patients with follicular synovitis. Conclusions: Overall, our data strongly support a pivotal role for RASF in the dysregulated production of pro-arthritogenic/inflammatory TSLP in the rheumatoid synovium, suggesting that the TSLP/TSLPR pathway contributes to chronic inflammation in RA. References: Koyama K, Ozawa T, Hatsushika K, Ando T, Takano S, Wako M, et al. A possible role for TSLP in inflammatory arthritis. Biochem Biophys Res Commun2007 May 25;357(1):99-104. Ozawa T, Koyama K, Ando T, Ohnuma Y, Hatsushika K, Ohba T, et al. Thymic stromal lymphopoietin secretion of synovial fibroblasts is positively and negatively regulated by Toll-like receptors/nuclear factor-kappaB pathway and interferon-gamma/dexamethasone. Mod Rheumatol2007;17(6):459-63. Disclosure of Interest: None Declared